Co-N4 anchored porphyrin-based COFs enable sacrificial-agent-free photocatalytic extraction of dispersed uranium resources - Chongheng Li; Jinjiao Pan; Yue Ma; Huazhen Rong; Yilei Zhang; Zhuoming Yang; Yifei Zhou; Chuan Gan; Yihui Yuan; Ning Wang (Desalination, 2026)

Carbonate rock-SRB system driven by high-concentration organic wastewater: Performance and mechanism for synergistic AMD remediation - Yisheng Mu; Jiajun Zou; Ruixue Zhang; Pan Wu; Shihong Zhang; Jiarui Zhu; Chuan Luo; Qiang Li (Journal of Environmental Chemical Engineering, 2026)

Multi-objective optimization of combustion chamber geometry and injection angle on the combustion and emission for an ammonia/hydrogen/diesel engine by the NSGA-III - Zhiqing Zhang; Zihao Song; Zhaoyang Li; Chuan Liu; Dongli Tan; Wensheng Yu; Yuguo Wang; Zibin Yin; Wenyuan Huang; Mingzhang Pan; Mingliang Chen; Bin Zhang (Fuel, 2026)

Unsaturated lactones from Aspergillus ochraceopetaliformis - Jing-Jie Bai; Hong-Qian Pan; Qiong Liu; Duo-Xiu Li; Bai-Chuan Zhu; Ying-Ming Zhang; Ai-Hong Zhao; Cheng-Shan Yuan (Natural Product Research, 2026)

Was the magma redox of the West Kunlun Paleo-Tethys modulated by surface environmental conditions of the Late Paleozoic Ice Age? - Zong-Yong Yang; Jing-Jing Zhu; Ruizhong Hu; Xian-Wu Bi; Li-Chuan Pan; Xing-Chun Zhang; Ju-Ting Deng; Yao-Wen Zhang; Qian Liu; Yi-Xin Li (Global and Planetary Change, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Evolution and role of manganese-transforming bacterial microorganisms during natural manganese-tailing succession - Chuan Wu; Yahui Wu; Jiahao Pan; Yangtao Lv; Waichin Li; Min Hu; Jun Wang; Shiming Su; Qi Zou; Shengguo Xue (Journal of Environmental Sciences, 2026)

Strong metal-support interaction regulated heterogeneous Fenton process for effective pollutants degradation - Chuan Wang; Xiang Zhang; Hongchao Li; Jiansheng Li; Jieshu Qian; Bingcai Pan (Chemical Engineering Journal, 2026)

Ediacaran separation of the North Qilian Block from the Central Qilian Block, NW China: Evidence from detrital zircon U-Pb geochronology - Lang Sun; Chuan Yang; Zhixin Sun; Jin Luo; Bing Pan; Chunlin Hu; Guoxiang Li; Maoyan Zhu (Journal of Asian Earth Sciences, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Investigation on parameter optimization and performance evaluation of the innovative hive-like shape sedimentation device for particle separation via numerical simulation: Improving efficiency and modular implementation - Chuan Pan; Weichao Ma; Chunran Zhang; Minghao Lu; Jiacheng Li; Jun Ma; Yong Ma; Lina Zhao; Liangchun Zhang (Journal of Environmental Chemical Engineering, 2026)

Manganese residue harmlessness with the combination of manganese mineralizing microbes, CaO and CO2 - Jiahao Pan; Chuan Wu; Yangtao Lv; Waichin Li; Jun Wang; Min Hu; Hongren Chen; Qi Zou; Shengguo Xue (Journal of Environmental Sciences, 2026)

Distribution of folate synthesis genes in Lactobacillaceae and characterization of high folate production - Zhihao Chen; Chuan Zhang; Yiyi Li; Chengcheng Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Qixiao Zhai; Fengwei Tian (Food Bioscience, 2026)

Gold metallogenesis in craton-margin settings: Insights from orogenic to supergene processes in the Ilesha Schist Belt, SW Nigeria - Yusuf Ademola Abdu‑Raheem; Jing-Jing Zhu; Abiola Omotayo Oyebamiji; Li-Chuan Pan (Acta Geochimica, 2026)

Study on the effect of ethylene oxide fumigation on the colonies of unearthed wooden cultural relics - Hui Li; Zeyu Pan; Chuan Yang; Meng Sun; Hui Jiang; Buyu Cao; Xingxia Ma (International Biodeterioration & Biodegradation, 2026)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Metabolic Responses and Oxidative Stress Adaptation Mechanisms of the Pituitary Gland in the Tiger Puffer Under Low-Temperature Stress - Yifan Li; Taicheng Li; Meihui Yao; Chuan Li; Zibin Jiang; Hongyu Pan; Wei Wang; Yajuan Li; He Zhou (Fishes, 2025)
To explore the induction of low temperature the Tiger Puffer (Takifugu rubripes) In this study, the influence of temperature on the pituitary gland during masculinization was investigated through chronic hypothermia stress experiments. Metabolomics was used to analyze the metabolic regulatory network of the pituitary gland under hypothermia stress. ELISA technology was employed to determine the activity content of oxidative stress-related enzymes in the pituitary gland. Further, TUNEL fluorescence labeling and qPCR were used to detect the apoptosis level of pituitary cells. Finally, to assess the impact of low-temperature stress on muscle tissue, HE staining and qPCR techniques were employed. The results showed that after 45 days of low-temperature stress, the differential metabolites of the pituitary gland were mainly enriched in the amino acid metabolic signaling pathway, and the contents of amino acids such as GSH and its synthetic precursors in the pituitary tissue changed significantly. The contents of oxidative stress indicators such as ROS and MDA all showed a trend of first increasing and then decreasing. The qPCR results of TUNEL fluorescence labeling and apoptosis-related genes were consistent, indicating that the apoptotic level of pituitary cells first increased and then decreased with the stress process. Histological analysis revealed that low temperature led to muscle cell atrophy and increased interstitial space in muscle tissue. The expression changes in genes related to muscle development further confirmed that low temperature significantly inhibited muscle growth and development. Therefore, this study speculates that after being subjected to chronic low-temperature stress, the pituitary gland of the red-finned Oriental pufferfish can alleviate the oxidative stress response of the body by strengthening the amino acid metabolic pathway, and the fish body has shown a physiological trend of gradually adapting to low-temperature stress, but the growth and development of muscles are still significantly inhibited. The results of this study can provide theoretical support for understanding the physiological adaptation mechanism of the red-finned Oriental pufferfish to low-temperature stress and lay a foundation for subsequent in-depth exploration of the pituitary response mechanism to low temperatures.

Development and performance evaluation of an anoxic-aerobic combined treatment system packed with carbonate rocks for acid mine drainage - Qiang Li; Ruixue Zhang; Jipei Ao; Pan Wu; Xiaoting Long; Chuan Luo (Journal of Water Process Engineering, 2025)

Integrated analyses of the Ediacaran-Cambrian boundary sequence in northern Gondwana (Anti-Atlas platform, Morocco) - Yiwei Xiong; Bo Chen; Xiaojuan Sun; Kai Chen; Ibtissam Chraiki; Aihua Yang; Chunlin Hu; zhixin Sun; Bing Pan; Chuan Yang; Tianchen He; Miao Lu; et al. (Gondwana Research, 2025)

U-Pb age and Lu-Hf isotopic compositions of zircon from tuff layers of the late Permian-Early Triassic sedimentary succession in the western Yangtze Block, SW China: Implications for the tectonic evolution and Impact of episodic volcanism on biotic recovery - Maoshan Chuan; Jiangtao Pan; Liang Wu; Dezong Li; Xinyuan Cao; Zhimou Yang; Zhi Ding; Ruxi Lin; Yong Cheng (Journal of Asian Earth Sciences, 2025)

Two-dimensional nitrogen-doped carbon nanosheets-coated porous SiO composites sponges for durable anode materials of high-energy lithium-ion batteries - Zaohong Zhang; Weichen Chen; Jie Tian; Kai Zhang; Carlos Ponce de León Albarrán; Chuan Wu; Zhicong Shi; Zibiao Li; Jia Hong Pan (Chemical Engineering Journal, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.

CFD-based flow simulation and optimization of horizontal tube sedimentation tanks (HTST) - Weichao Ma; Chunran Zhang; Chuan Pan; Minghao Lu; Jiacheng Li; Jun Ma; Yong Ma; Kena Qin (Process Safety and Environmental Protection, 2025)

Study of sludge dewatering conditioned by multivalent iron salt composite modified cinder and its reutilization - Weichao Ma; Chuan Pan; Chunran Zhang; Minghao Lu; Jiacheng Li; Jun Ma; Lina Zhao (Journal of Environmental Chemical Engineering, 2025)

Tectonic setting, paleoenvironment and REE source of the Lower Cambrian phosphorites, Yangtze Block (South China) - Chuan Guo; Yong Fu; Peng Xia; Zhen Yang; Yanjun Li; Zhongfei Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Stomatohabitans albus gen. nov., sp. nov., an oral living facultative anaerobic actinobacteria isolated form Steller sea lion, and proposal of Stomatohabitantaceae fam. nov. and Stomatohabitantales ord. nov - Zi-Wen Yang; Wen-Li Liu; Peng Zhang; Dan-Yuan Guo; Hong-Chuan Wang; Jia-Ling Li; Pan-Deng Wang; Gui-Xin Dong; Guo-Xing Nie; Wen-Jun Li (Systematic and Applied Microbiology, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Cambrian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Zhixin Sun; Lang Sun; Fangchen Zhao; Bing Pan; Malik Muhammad Saud Sajid Khan; Shehryar Ahmed; Chuan Yang; Lanyun Miao; Zongjun Yin; Guoxiang Li; Maoyan Zhu (Science China Earth Sciences, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Sublethal and transgenerational effects of lufenuron on the biological traits of Panonychus citri (McGregor) (Acari: Tetranychidae) - Meng-Hao Xia; Deng Pan; Chuan-Zhen Li; Yu-Chuang Li; Wei Dou; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2024)

Manipulating Li2O2 deposition morphology by surface spin modulation of cobalt-based spinel oxide catalysts in lithium−oxygen batteries - Yu Pan; Kun Li; Anjun Hu; Chuan Zhao; Yiming Zhang; Xiaoping Jiang; Baihai Li; Jun Wang; Jianping Long (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

A dual-timescale dynamics model for evaluating long-term profiles of distributed energy resources under multi-market mechanisms - Zhenyu Huang; Li Pan; Youbo Liu; Zhifang Yang; Xiaohui Wang; Chuan Yuan; Junyong Liu (Journal of Cleaner Production, 2023)

Heterogeneous Fenton water purification catalyzed by iron phosphide (FeP) - Shu-Chuan Mei; Liang Li; Gui-Xiang Huang; Xiao-Qiang Pan; Han-Qing Yu (Water Research, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

Estimation the effect of accumulated long-range transported pollutants during a PM2.5 event in Taiwan - Hsin-Chih Lai; Yu-Tung Dai; Lan-Phuong Le; Bo-Han Pan; Li-Wei Lai; Min-Chuan Hsiao (Atmospheric Pollution Research, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Bone Marrow Mesenchymal Stem Cells Reversed Ovarian Aging-related m6A RNA Methylation Modification Profile in Aged Granulosa Cells - Chuan Tian; Yuanyuan An; Jing Zhao; Xiangqing Zhu; Wei Wei; Guangping Ruan; Ye Li; Xinghua Pan (Stem Cell Reviews and Reports, 2023)
Background Ovarian ageing causes endocrine disturbances and the degeneration of systemic tissue and organ functions to seriously affect women's physical and mental health, and effective treatment methods are urgently needed. Based on our previous studies using juvenile rhesus monkey bone marrow mesenchymal stem cells (BMMSCs) to treat ovarian ageing in rhesus monkey, we found that BMMSCs improved ovarian structure and function. This study continues to explore the mechanism by which BMMSCs reversed granulosa cell (GC) ageing. Methods A GC ageing model and coculture system of BMMSCs were established, changes in the level of the N6-methyladenosine (m6A) methylation modification were detected, m6A-modified RNA immunoprecipitation sequencing (MeRIP-seq) were performed, correlations between m6A peaks and mRNA expression were determined, and the expression of hub genes was identified using Q-PCR, immunofluorescence staining, and western blot. Results Our results showed that H 2 O 2 successfully induced GC ageing and that BMMSCs reversed measures of GC ageing. BMMSCs increased the expression of the FTO protein and reduced the overall level of m6A. We identified 797 m6A peaks (348 hypomethylated and 449 hypermethylated peaks) and 817 differentially expressed genes (DEGs) (412 upregulated and 405 downregulated) after aged GCs were cocultured with BMMSCs, which significantly associated with ovarian function and epigenetic modification. The epigenetic repressive mark and important cell cycle regulator lysine demethylase 8 (KDM8) was downregulated at both the mRNA and protein levels, histone H3 was upregulated in aged GCs after BMMSC coculture, and KDM8 was upregulated after FTO was inhibited through FB23. Conclusions Our study revealed an essential role for m6A in BMMSCs in reversing GC ageing, and FTO regulated KDM8 mediates histone H3 changes may as a novel regulatory mechanism in BMMSCs to reverse GC ageing. Graphical Abstract

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Genesis of hydrous-oxidized parental magmas for porphyry Cu (Mo, Au) deposits in a postcollisional setting: examples from the Sanjiang region, SW China - Lei-Luo Xu; Jing-Jing Zhu; Ming-Liang Huang; Li-Chuan Pan; Ruizhong Hu; Xian-Wu Bi (Mineralium Deposita, 2023)

Effect of Frying on the Quality and Protein Degradation in Mugil cephalus : A Comparative Study of Vacuum and Atmospheric Frying - Huibo Wang; Zhisheng Pei; Qianwen Zheng; Pan Wen; Chuan Li; Yunsheng Xu; Changfeng Xue; Xiaoqin Wang; Xuanri Shen (Journal of Aquatic Food Product Technology, 2022)

Preparation of 2-Methoxyestradiol Self-emulsified Drug Delivery System and the Effect on Combination Therapy with Doxorubicin Against MCF-7/ADM Cells - Chuan Yu; Chen Li; Haofeng Pan; Tian Li; Suna He (AAPS PharmSciTech, 2022)

Millifolide A, a dimeric ether of degraded sesquiterpene lactones, inhibited the proliferation of human lung cancer cell line A549 - Pan-Pan Yu; Feng Yu; Wen-Zhe Li; Si-Ming Wang; Chuan Wang; Mei Dong; Zhi-Yu Ni; Yong Li; Hiromasa Kiyota (Natural Product Research, 2022)

Producing Biogas from Rice Straw: Kinetic Analysis and Microbial Community Dynamics - Shiyou Pan; Qiangqiang Liu; Chuan Wen; Zhenchong Li; Liqin Du; Yutuo Wei (BioEnergy Research, 2021)

The characterization and candidate gene isolation for a novel male-sterile mutant ms40 in maize - Xiaowei Liu; Yujing Yue; Zicheng Gu; Qiang Huang; Zijin Pan; Zhuofan Zhao; Mingmin Zheng; Zhiming Zhang; Chuan Li; Hongyang Yi; Tao Yu; Moju Cao (Plant Cell Reports, 2021)

Remelting of a Neoproterozoic arc root: origin of the Pulang and Songnuo porphyry Cu deposits, Southwest China - Dian-Zhong Wang; Ruizhong Hu; Pete Hollings; Xian-Wu Bi; Hong Zhong; Li-Chuan Pan; Cheng-Biao Leng; Ming-Liang Huang; Jing-Jing Zhu (Mineralium Deposita, 2021)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Six indicator genes for zinc (Zn) homeostasis in freshwater teleost yellow catfish Pelteobagrus fulvidraco: molecular characterization, mRNA tissue expression and transcriptional changes to Zn exposure - Guang-Hui Chen; Zhi Luo; Chuan-Chuan Wei; Dan-Dan Li; Ya-Xiong Pan (BioMetals, 2018)

Do aeration conditions affect arsenic and phosphate accumulation and phosphate transporter expression in rice (Oryza sativa L.)? - Chuan Wu; Qiongli Wang; Shengguo Xue; Weisong Pan; Laiqing Lou; Daojun Li; William Hartley (Environmental Science and Pollution Research, 2018)

Ocular Cubosome Drug Delivery System for Timolol Maleate: Preparation, Characterization, Cytotoxicity, Ex Vivo, and In Vivo Evaluation - Jiayuan Huang; Tingting Peng; Yanrong Li; Zhengwen Zhan; Youmei Zeng; Ying Huang; Xin Pan; Chuan-Yu Wu; Chuanbin Wu (AAPS PharmSciTech, 2017)

Down-Regulation of ClC-3 Expression Reduces Epidermal Stem Cell Migration by Inhibiting Volume-Activated Chloride Currents - Rui Guo; Fuqiang Pan; Yanping Tian; Hongli Li; Shirong Li; Chuan Cao (The Journal of Membrane Biology, 2016)

Simulation of runoff and nutrient export from a typical small watershed in China using the Hydrological Simulation Program–Fortran - Zhaofu Li; Hongyu Liu; Chuan Luo; Yan Li; Hengpeng Li; Jianjun Pan; Xiaosan Jiang; Quansuo Zhou; Zhengqin Xiong (Environmental Science and Pollution Research, 2015)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Sugar beet M14 glyoxalase I gene can enhance plant tolerance to abiotic stresses - Chuan Wu; Chunquan Ma; Yu Pan; Shilong Gong; Chenxi Zhao; Sixue Chen; Haiying Li (Journal of Plant Research, 2013)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Association of Heart Rate Variability of the Elderly with Personal Exposure to PM1, PM1–2.5, and PM2.5–10 - Li-Te Chang; Chin-Sheng Tang; Ying-Zu Pan; Chang-Chuan Chan (Bulletin of Environmental Contamination and Toxicology, 2007)

A simple, rapid and effective method for total RNA extraction from Lentinula edodes - Jun-hui Li; Chuan-hong Tang; Chun-yan Song; Ming-jie Chen; Zhi-yong Feng; Ying-jie Pan (Biotechnology Letters, 2006)